LEARNING MEDIA DEVELOPMENT OF THE GAME OF THE CROWN GAME IN THE CIVICS LESSON OF ELEMENTARY SCHOOL CLASS III - Raudhah Anisa Muslim; Munjiatun; Zariul Antosa (Yayasan Thaifah Manshurah Pekanbaru, 2023)
This research is motivated by the lack of learning media in the implementation of Civics learning, therefore the need for learning tools that support one of them is learning media. the media developed is interesting media, in accordance with the characteristics and needs of students. The purpose of this study was to determine the development and determine the feasibility of